Peculiarities of observing human rights in the conditions of emergency legal regimes caused by the pandemic - N. O. Rastorhuieva (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of the pandemic as a legal prerequisite for the introduction of certain mechanisms for the observance of human rights in the conditions of emergency legal regimes and to the identification of certain features of the observance and guarantee of these rights. A number of domestic and foreign legal acts regulating the introduction of the state of emergency have been analyzed. The main purpose of introducing a state of emergency has been determined. The list of reasons for restricting human rights has been analyzed and attention has been drawn to international experience in preventing this negative phenomenon.